2021
DOI: 10.3390/pr9081326
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-Up and Semi-Continuous Cultivation of Locally Isolated Marine Microalgae Tetraselmis striata in the Subtropical Island of Gran Canaria (Canary Islands, Spain)

Abstract: The goal of this study was to determine the feasibility of the large-scale cultivation of locally isolated Tetraselmis striata in different open ponds in Gran Canaria. The biomass productivities were 24.66 ± 0.53 kgDW in 32 days (28.9t/ha/year) for 8000 L indoors, 42.32 ± 0.81 kgDW in 43 days (38.8 t/ha/year) for an 8000 L pond outdoors, and 54.9 ± 0.58 kgDW in 28 days (19.6 t/ha/year) for a 45,000 L pond outdoors. The photosynthetic efficiencies were 1.45 ± 0.03% for an 8000 L pond indoors, 1.95 ± 0.04% for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Nevertheless, the ash content in this study is lower than in dried Arthospira harvested in natural lakes or cultivated in raceway systems set outdoors or under greenhouse conditions in other arid/semi-arid areas [23,25,48]. This is possibly because of the effective rinsing of the algal slurry [25,59], or thanks to the (more efficient) greenhouse protection from dust accumulation in the culture [86].…”
Section: Biomass Profile and Qualitymentioning
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, the ash content in this study is lower than in dried Arthospira harvested in natural lakes or cultivated in raceway systems set outdoors or under greenhouse conditions in other arid/semi-arid areas [23,25,48]. This is possibly because of the effective rinsing of the algal slurry [25,59], or thanks to the (more efficient) greenhouse protection from dust accumulation in the culture [86].…”
Section: Biomass Profile and Qualitymentioning
confidence: 61%
“…In parallel, several studies under laboratory conditions have revealed the negative or even lethal impact of high concentrations of Fe, Cu, Zn, Ni and Cd added in the culture media on A. platensis growth and cellular contents, and the fast accumulation of these metals in the biomass at concentrations up to one order of magnitude higher than the control, due to the high biosorption capacity of Arthrospira cells [94][95][96]. In this study, protection of the greenhouse from external agents may have also played a beneficial role in maintaining low heavy metal content and microbial load during long-term cultivation [86], since soil and dust are potential vectors responsible for heavy metal accumulation and airborne pathogen presence in algal cultures [18,23]. Phytonutrient content did not vary significantly between the experimental phases F and R, and was quite constant along the cultivation period (Figures 3 and A3, Appendix B), which is in line with the biochemical composition consistency of the biomass in wellmanaged open production systems [18].…”
Section: Biomass Profile and Qualitymentioning
confidence: 97%
“…Additionally, Tetraselmis species have been found to show a wide spectrum of antimicrobial activity, while their high vitamin E contents have also been proposed as suitable for human and animal consumption [ 13 ]. They are also a source of natural pigments (violaxanthin, lutein and β-carotene), which have nutraceutical and cosmetic applications [ 14 ]. Additionally, Tetraselmis chuii was recently approved as a novel food for human consumption [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are also a source of natural pigments (violaxanthin, lutein and β-carotene), which have nutraceutical and cosmetic applications [ 14 ]. Additionally, Tetraselmis chuii was recently approved as a novel food for human consumption [ 14 ]. Therefore, this genus is of high research interest and its ability to withstand high temperatures and salinities makes it a suitable candidate for large-scale cultivation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation